The Interactive Effect of Goal Attainment and Goal Importance on Acculturation and Well-Being - Toth-Bos, Agnes; Wisse, Barbara; Farago, Klara (Frontiers in Psychology, 2020)
The purpose of the present research is to shed light on whether and how migrants’ goal pursuit relates to their acculturation and well-being. Previous research has demonstrated the beneficial role that striving for and attaining intrinsic goals has for well-being. Yet, the relationship between the pursuit of intrinsic goals and acculturation has hardly been addressed. To fill this void, we investigated whether migrants’ acculturation and well-being can be seen as a function of their pursuit of intrinsic goals. We posited that the attainment of intrinsic goals would positively predict migrants’ level of acculturation and subsequent well-being, particularly when migrants deemed these goals to be important. We tested our hypotheses in two scenario studies and two field-studies. In all four studies we confirmed our hypothesis that migrants’ intrinsic goal attainment and well-being (measured by satisfaction with life and by anxiety is mediated by their acculturation level. However, in only two of the four studies did we find support for our hypothesis that the relationship between intrinsic goal attainment and acculturation is moderated by intrinsic goal importance. We discuss the theoretical importance and the practical consequences of our findings. Furthermore, we outline future research directions that could deepen understanding of the relationship between migrants’ goal pursuit and their acculturation.